Indigenous pigs of Arunachal Pradesh: outstanding prospective for pork production-preliminary observations - Kalita, Dipankar (Journal of Livestock Biodiversity, 2025)
The paper provides preliminary observations on various aspects of indigenous pigs of Arunachal Pradesh. Arunachal Pradesh is entirely a hilly state inhabited by a large number of tribes. The people of Arunachal Pradesh rear pig not only for food but also for sacrifice for ritual purposes. Pig is the main animal in this region and it can be maintained easily without much care and cost intensive management practices. Rural people consume pork meat as an easy source of protein being produced from backyard farming. Arunachal local pigs are compact, small in size, pot bellied in appearance, hairy coat, mostly black body color with white spots on legs, around shoulder region, at belly, and at fore head. Arunachal local pigs show extensive disease resistance or tolerance capacity against infectious and non infectious diseases. Male and female attain their sexual maturity at very early age in comparison to other variety and breeds of pigs in the country. The approximate price of an adult pig with live body weight of about 40 kg ranges from Rs 7000/-  to Rs 9000/-, irrespective of the sex. There is a definite need to characterize and evaluate this unique germplasm, accredit it as a new pig breed of the country and initiate programmes for its improvement and sustainability.